Analysis of experience, safety and prospects of diversification of nuclear fuel at nuclear power plants - Skalozubov, Vladimir; Melnik, Serg; Pantak, Oksana; Gryb, Vitalii; Spinov, Vladyslav; Komarov, Yurii (Technology audit and production reserves, 2019)
The object of research is the design fuel assemblies (FA-A) at nuclear power plants with water-cooled water reactors located in Ukraine. The analysis of the experience and prospects of diversification of design fuel assemblies of pressurized water reactors with alternative heat generating assemblies of Westinghouse Electric Company is carried out. The analysis is carried out on the basis of measures and results of diversification of fuel assemblies at the Temelin nuclear power plant (Czech Republic), as well as the South Ukrainian and Zaporizhzhia nuclear power plants (Ukraine). As a result of the analysis, it is shown that the diversification of design fuel assemblies by alternative heat assemblies by Westinghouse Electric Company provides the necessary nuclear safety conditions for the maximum allowable temperature of the gratings of fuel rods and the temperature of nuclear fuel. The work determines the need for additional analysis of nuclear safety and reliability of the reactor loop equipment in relation to the conditions of critical hydrodynamic shock during the diversification of fuel assemblies. It is revealed that the known results of nuclear safety analysis during diversification of fuel assemblies by traditional accident modeling approaches are not sufficiently substantiated. And they also significantly depend on the negative effects of «differences in the results of accident modeling by different users of the same codes» and «differences in the results of accident modeling by different codes». In addition, well-known deterministic codes do not simulate the conditions and consequences of hydrodynamic shock and various types of thermohydrodynamic instability in the reactor loop. It is shown that it is necessary to develop alternative methods for analyzing nuclear safety and equipment reliability of systems important to safety in diversifying fuel assemblies that are independent of the above negative effects. A calculation analysis of the influence of the coolant speed on the external heat transfer coefficients determined that the safety conditions for the permissible temperature of the Westinghouse Electric Company fuel rods are provided up to a maximum design temperature of 90 °C in safety heat exchangers.